The effectiveness of an integration based training program in developing interdisciplinary thinking skills and students’ attitudes towards transdisciplinary projects - Ali Omar, Ali Alwardany; Saleh, Walaa Saleh Megahed; Ebrahim, Mona Abdelmoneim; Torki, Marwa; Hamoudah, Noha; Ahmed Ali, Manal ElSayed (Research Journal in Advanced Humanities, 2026)
This research aims to investigate the effectiveness of an integration-based training program in developing interdisciplinary thinking skills and students' attitudes towards Transdisciplinary Projects. To achieve this, a quasi-experimental design with a single group and pre- and post-testing was used. The measurement tools consisted of an interdisciplinary thinking skills test and an attitude questionnaire towards Transdisciplinary Projects. The research was conducted with a group of (60) first-year students at the College of Public Health, Imam Abdulrahman Bin Faisal University, Kingdom of Saudi Arabia, during the second semester of the academic year (2024-2025). The research yielded several results, most notably that the integration-based training program contributed to developing interdisciplinary thinking skills and improving students' attitudes towards Transdisciplinary projects. This has already led to their inclusion in the curriculum of some courses. Based on these results, the research recommends a set of recommendations